Anti-Inflammatory and Immunomodulatory Properties of Inorganic Fullerene-Like Tungsten Disulfide Nanoparticles in the Culture of Human Peripheral Blood Mononuclear Cells - Snežana Zečević; Darinka Popović; Sergej Tomić; Marina Bekić; Sara Rakočević; Maja Kosanović; Dušica Stojanović; Petar Uskoković; Milan Marković; Dejan Bokonjić; Miodrag Čolić (Nanomaterials)
Tungsten disulfide (WS2) nanoparticles have emerged in the biomedical field as potential theranostic agents due to their unique properties, including biocompatibility. However, their impact on the immune response remains unexplored. This study aimed to evaluate the effects of inorganic fullerene-like WS2 (IF-WS2) nanostructures on human peripheral blood mononuclear cells (PBMCs) in vitro. The study investigated several parameters to evaluate the effects of IF-WS2 nanoparticles. Cytotoxicity was assessed by measuring cell viability, apoptosis, and necrosis. Internalization of IF-WS2 by PBMCs was analyzed using morphological and flow cytometric techniques. Proliferation was studied in CellTrace Far Red-prestained total PBMCs stimulated with phytohemagglutinin (PHA) and in isolated T cell cultures stimulated with CD3/CD28-coated beads. Additionally, the production of cytokines and chemokines was measured in culture supernatants of total PBMCs and T cells. IF-WS2 nanoparticles were non-cytotoxic up to a concentration of 200 µg/mL. Concentrations ≥25 µg/mL inhibited PHA-stimulated PBMC proliferation but did not affect T cell proliferation. Morphological and flow cytometric analysis demonstrated dose- and time-dependent internalization of IF-WS2 by macrophages. Additionally, IF-WS2 significantly reduced the production of pro-inflammatory cytokines (IL-1β, TNF-α, IL-8, MCP-1, and GRO-α) in PHA-stimulated PBMCs. Th1, Th17, and Th21 cytokines were downregulated, while Th2, Th9, and T regulatory cytokines were upregulated. In conclusion, this study demonstrated for the first time that pristine IF-WS2 nanoparticles, at non-cytotoxic concentrations, exhibit notable anti-inflammatory and immunomodulatory properties on activated PBMCs in vitro.